The literature of satire - Knight, Charles A. (Cambridge University Press, 2004)
Ranging from the classics to the present, Charles Knight provides illuminating readings of such satirists as Horace, Lucian, Jonson, Molière, Swift, Pope, Flaubert, Ostrovsky, Kundera, and Rushdie in this study of satire in plays, novels, newsprint and verse. His broad examination sheds new light on the nature and functions of satire as a mode of writing